Partial volume effect in SPECT & PET imaging and impact on radionuclide dosimetry estimates - Marquis, H; Willowson, K P; Bailey, D L (Asia Oceania journal of nuclear medicine & biology, 2023)
The spatial resolution of emission tomographic imaging systems can lead to a significant underestimation in the apparent radioactivity concentration in objects of size comparable to the resolution volume of the system. The aim of this study was to investigate the impact of the partial volume effect (PVE) on clinical imaging in PET and SPECT with current state-of-the-art instrumentation and the implications that this has for radionuclide dosimetry estimates. Using the IEC Image Quality Phantom we have measured the underestimation in observed uptake in objects of various sizes for both PET and SPECT imaging conditions. Both single pixel measures (i.e., SUV ) and region of interest mean values were examined over a range of object sizes. We have further examined the impact of the PVE on dosimetry estimates in OLINDA in Lu SPECT imaging based on a subject with multiple somatostatin receptor positive paragangliomas in the head and neck. In PET, single pixel estimates of uptake are affected for objects less than approximately 18 mm in minor axis with existing systems. In SPECT imaging with medium energy collimators (e.g., for Lu imaging), however, the underestimates are far greater, where single pixel estimates in objects less than 2-3×the resolution volume are significantly impacted. In SPECT, region of interest mean values are underestimated in objects less than 10 cm in diameter. In the clinical case example, the dosimetry measured with SPECT ranged from more than 60% underestimate in the largest lesion (28×22 mm in maximal cross-section; 10.2 cc volume) to >99% underestimate in the smallest lesion (4×5 mm; 0.06 cc). The partial volume effect remains a significant factor when estimating radionuclide uptake in vivo, especially in small volumes. Accurate estimates of absorbed dose from radionuclide therapy will be particularly challenging until robust solutions to correct for the PVE are found.